The development of hyperactive boys: A 12-year follow-up. - Claude, Diane. (University of Ottawa (Canada), 1993)
The present 12-year follow-up study was conducted to investigate the long-term development of 60 hyperactive children, who were further subdivided onto those with and without childhood aggressiveness. They were followed from childhood to late adolescence/early adulthood, and compared on psychiatric, cognitive, and academic outcome with that of 60 matched normal control subjects. Childhood predictors of poor outcome were also explored in the hyperactive group. Consistent with previous studies, the core deficits of hyperactivity persisted in more than half of the hyperactive group. However, the results called into question the widespread claim that childhood hyperactivity was related to antisocial behaviours in adolescence. Although the hyperactive group displayed significantly more Antisocial Personality Disorder, Drug Use Disorders and comorbidity than the control group in adolescence, these group differences were significantly attributable to the aggressive subgroup of hyperactive subjects. In contrast, adolescents who were hyperactive only in childhood did not differ significantly from the control group in psychiatric functioning, except for their persistent ADHD. The hyperactive/aggressive subgroup had received the most individual and residential treatment for their behaviour problems. Consistent with previous research, at follow-up, hyperactive subjects displayed significantly poorer spelling, arithmetic and reading comprehension skills than did the control group. In comparison with the control group, the hyperactive group had also completed fewer years of High School education, failed more courses, received more special services in High School and fewer of them had attended post-secondary school. Hyperactive/aggressive and hyperactive only subgroups generally displayed similar problems on these academic variables. These preliminary findings suggest that chronicity of hyperactive behaviours is in part determined by its severity in childhood. Overall, the present findings suggest that hyperactivity is persistent in a significant number of children and the heterogeneity of ADHD needs to be addressed in order to move towards a better understanding of the long-term development of children with ADHD. (Abstract shortened by UMI.)
Keywords: Psychology, Developmental.